Comprehensive Analysis of Virulence Genes, Antibiotic Resistance, Biofilm Formation, and Sequence Types in Clinical Isolates of Klebsiella pneumoniae - Mohsen Nazari; Jaber Hemmati; Babak Asghari (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: K. pneumoniae demonstrates notable biofilm-associated antibiotic resistance, supported by a significant association with XDR strains, along with a diverse array of virulence gene profiles. The study underscores the importance of understanding molecular epidemiology for effective management of hospital infections, emphasizing the need for targeted surveillance and infection control measures.